(untitled) (Comparatismi, 2023)
The essay analyses the way in which emotions are represented within the new international media landscape, through the American television series Grey’s Anatomy, conceived by Shonda Rhimes and still broadcast today since 2005. Seasons after seasons, Grey’s Anatomy presents itself as an antidote to cynicism and indifference, representing the primary emotions painted through a strong bodily and visual component. Initially the emotions bring imbalance within the universe of the protagonist Meredith, who is confronted with the cumbersome image of a mother-surgeon, selfish and perfectionist, and an absent and weak alcoholic father: her inability to create positive bonds and her fear of abandonment will change towards a positive and at the same time always restless dimension which will be represented through the desire transposed in the narration.